The Impact of Profitability, Company Size Asset Growth On The Capital Structure - Jibrail, Ahmad; Akbar, Arya Zulfikar; Hartini, Hartini (Indonesian Business Review, 2024)
The objective of this study was to assess and examine the impact of profitability, business size, and sales growth on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2022. The study encompassed a total of 140 manufacturing businesses that were listed on the Indonesia Stock Exchange over the period from 2018 to 2022. The employed sample approach is purposive sampling. The analysis technique employed utilises the IBM SPSS (Statistical Package for Social Science) programme, specifically version 20. The findings indicated that profitability, firm size, and sales growth exerted a favourable and statistically significant impact on the capital structure. The implication of this research is that company management should prioritise enhancing performance by focusing on profit management, making informed decisions to achieve sustainable profits, efficiently and effectively controlling costs, and effectively managing resources to foster continuous growth and development into a large company. Choosing the appropriate finance source for the company's operating activity.